Exercise behavior and quality of life of the elderly in Northeastern, Thailand - Namvicha, Kittisak; Sujayanont, Patcharawan; Kwuansawat, Thidarat; Nithikathkul, Choosak (Edelweiss Applied Science and Technology, 2025)
Exercise has been demonstrated to be crucial for promoting health and quality of life among the elderly population, encompassing physical, mental, social, and cognitive aspects. However, there remains a paucity of information regarding exercise behavior and associated factors in Buriram Province. This descriptive research aimed to investigate exercise behavior and quality of life among the elderly population in Buriram Province. The study sample comprised 577 elderly individuals, selected through multistage random sampling. Data were collected between August and November 2024 using questionnaires and interviews, with a reliability coefficient of 0.79 and an IOC value of 1.00. Data analysis was conducted using descriptive statistics, the chi-square test, Pearson's correlation, and multiple regression. The majority of elderly individuals exhibited a high level of exercise behavior (59.10%). Key factors influencing exercise behavior included attitudes, monthly income, and chronic illnesses, with attitudes emerging as the most significant predictor. Overall, the quality of life ranged from good to very good across all assessed aspects. Elderly individuals with positive attitudes demonstrated consistent exercise behavior and improved quality of life.